SLEEP AND PHYSICAL RECOVERY METHODS IN SPORT: A NARRATIVE REVIEW - Nesterak, Wiktor; Suchecka, Julia; Szubert, Izabela; Lamorski, Jakub; Stępień, Gabriela; Chudecka, Karolina; Chylewski, Michał; Józwa, Katarzyna; Kędzierska, Aleksandra; Przewoźna, Urszula (International Journal of Innovative Technologies in Social Science, 2026)
Recovery is a fundamental component of athletic training and performance. Appropriate recovery strategies support physiological adaptation, reduce fatigue, and decrease the risk of injury. Among the various recovery approaches used in sport, sleep and physical recovery methods are the most commonly applied by athletes and coaches. The aim of this narrative review was to evaluate the role of sleep and selected physical recovery methods in post-exercise recovery. A literature search was conducted using electronic databases, including PubMed and Google Scholar. Original studies, systematic reviews, meta-analyses, and narrative reviews related to sleep, cold-water immersion, massage, stretching, and foam rolling were analyzed. Current evidence indicates that sleep is the most important recovery factor, as it directly influences hormonal regulation, immune function, glycogen restoration, protein synthesis, cognitive performance, and overall adaptation to training. Adequate sleep has been associated with improved reaction time, endurance, concentration, and reduced injury risk. In contrast, physical recovery methods appear to be effective mainly in reducing delayed onset muscle soreness and perceived fatigue, while their influence on physiological recovery mechanisms remains limited. Methods such as cold-water immersion, massage, stretching, and foam rolling may improve subjective recovery and readiness for subsequent exercise sessions. The findings suggest that sleep should be prioritized as the primary recovery strategy, whereas physical recovery methods should be considered complementary interventions. A combined recovery approach may provide the greatest benefits for athletic performance and long-term adaptation.